Phenomenology of certainty and belief. Reading William James - Flavia Stara (Ricerche di Pedagogia e Didattica, 2014)
This essay studies the analysis that the psychologist and philosopher WilliamJames applies to the function of belief in relation to his concepts of the stream ofthought and process of knowledge. Furthermore, it pays attention to James’s phenomenologyof certainty within experience and to the explanation of the foundationalplace of feelings in experience. In James’s thought we may call certainty onlywhat can provide a knowledge which stands in immediate relation to the innerstate: the images provided by individual depths are both the locus of perplexityand the spring of certainty. The truth of beliefs is in this sense provisional uponthe outcome of the continuing experience of understanding and of the continuingprocess of critical scrutiny.